Tarzan and the jewels of Opar - Burroughs, Edgar Rice, 1875-1950 (Burroughs, Edgar Rice, 1875-1950. Tarzan novels, 2003)
Here Tarzan returns to Opar, the source of the gold for lost Atlantis. Ages ago Atlantis sunk beneath the waves -- but the denizens of Opar still mine the gold of this lost colony. Tarzan, following greedy pair -- one Belgian, one Arab -- into the jungle, where they stumble into the lost city. Bad enough -- and then Tarzan injures his head in a fight and loses his memory. That's great news for La, the high priestess for the Flaming God, who's had a serious crush on the apeman since their first encounter. But the priests who work for her have other ideas: they don't intend to allow Tarzan to escape their sacrificial knives a second time. ...